Aves y garrapatas (un asunto que pica) - TARRAGONA, EVELINA LUISA; FLORES, FERNANDO SEBASTIÁN; VENZAL, JOSÉ MANUEL; NAVA, SANTIAGO; LAMATTINA, DANIELA (Revista Aves Argentinas, 2025)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).